Efeito da escaldadura-das-folhas em um campo comercial de cana-de-açúcar no Brasil e reação de variedades - González, Claudia Elizabeth Bogado (Universidade Federal de São Carlos, 2023)
Leaf scald (LSD) in the sugarcane industry in Brazil is a disease that, despite its prevalence in all producing regions of the country, has received insufficient attention. This disease, caused by the bacterium Xanthomonas albilineans, represents a significant risk to crops due to its ability to spread quickly, mainly due to its latency state, which makes it a threat, especially in planting materials. In Brazil, there is no information about the damage caused by LSD in the country's commercial plantations, which has led to an underestimation of its impacts on the quality and production of the crop. However, it is important to highlight that studies have been carried out in other countries that highlighted the negative impact of LSD on reducing productivity. Therefore, it is essential to understand in detail the effect of LSD on Brazilian commercial plantations. At a global level, the use of resistant varieties is recommended as the main strategy to control the disease. However, due to the lack of sufficient information about the resistance or susceptibility of sugarcane varieties grown in Brazil, producers have difficulty opting for this control method. For this reason, the objectives of the work were to determine the effect of leaf scald on a commercial sugarcane plantation in Brazil and the reaction of the varieties. The comparison between two nearby fields of the same variety allowed us to estimate an incidence of LSD of 61% in the affected field, death of setts of 48.5% and weight loss of clumps of 57%. Furthermore, through decapitation inoculation, varieties RB92579 and RB966928 were classified as the most susceptible, while varieties RB975033, RB975952 and RB985476 were identified as the most resistant.
Effect of scald-of-folhas in a commercial sugar cane field in Brazil and variety reaction
Keywords: Inoculação; Resistência; Saccharum spp; Xanthomonas albilineans; Inoculation; Resistance; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE::FITOPATOLOGIA